Structural, electrical, and dielectric properties of Cr doped ZnO thin films: Role of Cr concentration - Gurbuz, Osman; Okutan, Mustafa (ELSEVIER SCIENCE BV, 2016)
An undoped zinc oxide (ZnO) and different concentrations of chromium (Cr) doped ZnO CrxZnO1-x (x = 3.74, 5.67, 8.10,11.88, and 15.96) thin films were prepared using a magnetron sputtering technique at room temperature. These films were characterized by X-ray diffraction (XRD), High resolution scanning electron microscope (HR-SEM), and Energy dispersive X-ray spectrometry (EDS). XRD patterns of all the films showed that the films possess crystalline structure with preferred orientation along the (100) crystal plane. The average crystallite size obtained was found to be between 95 and 83 nm which was beneficial in high intensity recording peak. Both crystal quality and crystallite sizes decrease with increasing Cr concentration. The crystal and grain sizes of the all film were investigated using SEM analysis. The surface morphology that is grain size changes with increase Cr concentration and small grains coalesce together to form larger grains for the Cr11.88ZnO and Cr15.96ZnO samples. Impedance spectroscopy studies were carried out in the frequencies ranging from 5 Hz to 13 MHz at room temperature. The undoped ZnO film had the highest dielectric value, while dielectric values of other films decreased as doping concentrations increased. Besides, the dielectric constants decreased whereas the loss tangents increased with increasing Cr content. This was considered to be related to the reduction of grain size as Cr content in ZnO host material increased. Furthermore, by increasing the Cr concentration, the improved electrical performance was observed. The electrical resistivity of samples decreased from 3.98 x 10(-2) Omega cm to 4.03 x 10(-4) Omega cm with the increase in Cr content. For these reasons, Cr doped ZnO (Cr:ZnO) thin films may be used in microwave devices as the electrical conductivity increases while dielectric constant decreases with the Cr content. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Cr doped ZnO; RF magnetron sputtering; Dielectric constant; Electrical conductivity; OPTICAL-PROPERTIES; MAGNETIC-PROPERTIES; ANNEALING TEMPERATURE; CO; CONDUCTIVITY; TRANSPARENT; MORPHOLOGY; THICKNESS; FIELD; SIZE; Chemistry; Materials Science; Physics